The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/adma.202405178
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Band Structure via Combined Molecular Orbital and Lattice Symmetries in a Surface‐Confined Metallated Graphdiyne Sheet

Ignacio Piquero‐Zulaica,
Wenqi Hu,
Ari Paavo Seitsonen
et al.

Abstract: Graphyne (GY) and graphdiyne (GDY)‐based monolayers represent the next generation two‐dimensional (2D) carbon‐rich materials with tunable structures and properties surpassing those of graphene. However, the detection of band formation in atomically thin GY/GDY analogues has been challenging, as both long‐range order and atomic precision have to be fulfilled in the system. Here, we report direct evidence of band formation in on‐surface synthesized metallated Ag‐GDY sheets with mesoscopic (∼1 µm) regularity. Emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…Although various OMNs have been constructed with selected molecular building blocks via consuming surface adatoms provided by the substrate underneath, the success rate for their realization is often unforeseeable and strongly substrate-dependent, limiting the general applicability of such functional organometallic materials. In particular, it has recently been shown that extended graphdiyne-like, alkynyl–silver–alkynyl, and alkynyl–gold–alkynyl honeycomb OMNs can be prepared successfully by applying on-surface synthesis strategies. Yet, the large spectrum of metal centers and possible organic linkers calls for the identification of efficient routes to bestow the desired variety and versatility to the structural and electronic properties of such films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although various OMNs have been constructed with selected molecular building blocks via consuming surface adatoms provided by the substrate underneath, the success rate for their realization is often unforeseeable and strongly substrate-dependent, limiting the general applicability of such functional organometallic materials. In particular, it has recently been shown that extended graphdiyne-like, alkynyl–silver–alkynyl, and alkynyl–gold–alkynyl honeycomb OMNs can be prepared successfully by applying on-surface synthesis strategies. Yet, the large spectrum of metal centers and possible organic linkers calls for the identification of efficient routes to bestow the desired variety and versatility to the structural and electronic properties of such films.…”
mentioning
confidence: 99%
“…22 This article is licensed under CC-BY 4 Organometallic bonding, mostly involving carbon−metal linkages, due to its generally covalent nature 23 and the reversibility associated with the binding characteristics, 24 may provide a powerful strategy for engineering surface-confined organic networks with appreciable robustness as well as impressive mesoscale regularity. 25,26 2D organometallic networks (OMNs) feature functional 2D materials with a significant promise. The often higher flexibility relative to purely covalent linking and the reversibility during the formation process in the low-dimensional environment of a surface offer the possibility of self-healing of defects, potentially affording higher order and tailored packing motifs and symmetry.…”
mentioning
confidence: 99%